Identifying ancestral wheat introgressions and traits for improved tolerance to hostile soils - Jaswant Singh, . (2018)
Wheat is the third most widely consumed crop after rice and maize globally. The Green Revolution increased the Indian wheat production tremendously since the 1960s using semi-dwarf wheat varieties and subsequent trait-based breeding under non-hostile soils. In addition to grain yield, wheat is an important source of dietary zinc (Zn) and other mineral elements in many countries. Dietary Zn deficiency is widespread, especially in developing countries, and there are wide scale efforts to breed wheat with increased grain Zn concentrations in South Asia. It is not clear if further grain yield and quality traits such as grain Zn concentration improvements can be sustained due to 1) narrow genetic diversity in modern wheat, and 2) limited land availability e.g., many soils are marginal due to salinity, alkalinity, acidity and mineral nutrient imbalances. The first aim of this thesis was to quantify grain yield and yield components, including juvenile root traits, and grain Zn concentration of a panel of 36 Indian diverse wheat genotypes to explore the potential for site specific trait selection for hostile soils and characterise the baseline effect of genotype (G), site (E), and genotype x site interaction (G*E) under a wide range of soil conditions. Mean grain yields ranged from 1.0 to 5.5 t ha-1 at hostile and non-hostile sites, respectively. G*E interactions affected many yield and component traits, which support the value of site-specific traits selection for hostile soils. The mean grain Zn concentration of 36 genotypes ranged from 25 to 35 mg kg-1. Despite a relatively small overall contribution of G to the overall variation in grain Zn concentration, biofortifying wheat through breeding is likely to be effective at scale given that some genotypes (e.g. Kharchia 65) performed consistently across diverse soil types. Root angle and lateral root traits were associated with grain yield and some mineral composition traits. The second aim of this thesis was to study the performance of eight amphidiploids derived from Thinopyrum bessarabicum, a tall wheat grass, for yield, yield components and grain Zn concentration under saline soils. Reduction in GYD in amphidiploids were less than in Indian genotypes under saline soils and grain Zn concentration ranged from 36-43 mg kg-1. The third aim of this thesis was to explore wild wheat relatives, non-relatives and their derivatives to increase the genetic diversity for grain Zn concentration. The mean grain Zn concentration of 225 wild wheat accession ranged from 47 to 178 mg kg-1. Notably, Amblyopyrum muticum, derived amphidiploids and double haploid lines could be useful sources of grain Zn variation that can be used in breeding programmes to increase the grain Zn concentration in modern wheat varieties to alleviate the dietary Zn deficiency.